1991
DOI: 10.1152/ajprenal.1991.261.5.f831
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous localization of G protein alpha-subunits in rat kidney

Abstract: The Gs alpha and Gi alpha 1-3 subunits of GTP-binding proteins were localized in sections of rat kidney using antibodies against unique synthetic decapeptides from the different G alpha subunits. All of the G alpha subunits were found to have a polarized distribution on renal tubule epithelial cells, and staining was typically found on either basolateral or apical membranes in a given cell type. Gi alpha 1 was localized to the apical pole of both thick ascending limb cells and cells forming the papillary epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…G␣ subunits are localized on the plasma membrane as well as on intracellular membranes such as Golgi membranes (36)(37)(38), as shown here for G␣i3-GFP (see Fig. 3B), where they regulate vesicular trafficking (39,40).…”
Section: Figsupporting
confidence: 59%
“…G␣ subunits are localized on the plasma membrane as well as on intracellular membranes such as Golgi membranes (36)(37)(38), as shown here for G␣i3-GFP (see Fig. 3B), where they regulate vesicular trafficking (39,40).…”
Section: Figsupporting
confidence: 59%
“…Interestingly, this is the site where the majority of GPCRs and many G proteins (43,44) are located in these cells, suggesting that GIPN could be part of a GPCR͞G␣͞ RGS-GAIP signaling complex. The presence of two different cross-immunoreactive species in cytosolic (38 kDa) and membrane (Ͼ94 kDa) fractions from mouse kidney raises the question of the relationship between the two forms.…”
Section: Discussionmentioning
confidence: 99%
“…The partial overlap with Man II suggested that Gets and Geti3 may be associated with Golgi membranes of the pancreatic exocrine cell. Since G~i3 had been previously localized to the Golgi in other cell types (53,60) and information on the localization of Gas is more limited, we focused on Get s and compared its distribution in the Golgi to that of 13-COP, ARF, and caveolin, proteins with unique Golgi localizations. Staining for the coatamer components (28, 51) 13-COP ( Fig.…”
Section: Heterotrimeric a Subunits Gas And Gat~ Are Found In The Col#mentioning
confidence: 99%